The Effects of Swimming on Scopolamine Induced Hippocampal Oxidative Stress in Long-Evans Rats (Central Medical College Journal, 2025)
Background: Scopolamine causes oxidative stress by accelerating the buildup of reactive oxygen species. Physical exercise, such as swimming use oxygen more efficiently, provides benefits in oxidative stress. Objective: To evaluate the effects of swimming on scopolamine induced hippocampal oxidative stress in Long-Evans rats. Methods: This experimental study was conducted in BMU. For this purpose, 18 Long-Evans rats aging 8 to 10 weeks and having body wt. 175±25 grams were collected from animal house of this University. On the basis of treatment, rats were divided into group I (6 rats treated with oral normal saline 5 ml/kg body wt.), group II (6 rats treated with scopolamine), and group III (6 rats treated with scopolamine and allowed to do swimming exercise) for 14 consecutive days. For estimation of hippocampal oxidative stress, reduced glutathione (GSH) & malondialdehyde (MDA) levels were measured by ELISA. Data were expressed as mean ±SEM and statistical analysis was done by using SPSS version 22. Statistical tests were carried out by ANOVA followed by Bonferroni’s post hoc test. In the interpretation of results, p≤0.05 was considered as significant. Results: In perspective  of hippocampal enzymes assay, GSH level significantly lower (p≤0.05) and MDA level significantly higher (p≥0.05) was found in group II rats when compared to group I rats. But GSH level significantly higher (p≤0.05) and MDA level significantly lower (p≤0.05) in group III rats, when compared to group II rats. Additionally, their levels were almost similar in group III in comparison to those of group I. Conclusion: Swimming can prevent scopolamine induced hippocampal oxidative stress in Long-Evans rats. Central Medical College Journal Vol 9 No 1 January 2025 Page: 37-43